Uterine Performance of Rats Exposed to Cigarette Post-Therapy Ethanol Extract of Kebar Grass (Biophytum petersianum Klotzsch) - Unitly, Adrien Jems Akiles; Kaihena, Martha; Kubela, Dormatina (Green Publisher Indonesia, 2023)
This study aims to determine the effect of giving ethanol extract of kebar grass (Biophytum petersianum Klotzsch) on the uterine performance of Rattus norvegicus rats exposed to cigarette smoke. The experimental design used was a completely randomized design (CRD). The results obtained were analyzed by Analysis of Variance (ANOVA) then continued with Duncan's test at a significant level of α = 0.05 using SAS software. The sample consisted of 12 rats, which were divided into 4 groups. The rat group (+), 0.067, 0.0135, decreased uterine function by exposure to 10 cigarettes/head/day for 28 days. Mice (-) were the negative control group, namely rats that were not exposed to cigarette smoke and ethanol extract of coriander grass. Mice (+) are the positive control group, namely rats exposed to cigarette smoke 10 cigarettes/head/day for 28 days. Groups 0.067 and 0.135 were exposed to cigarette smoke 10 cigarettes/head/day for 28 days and then given 0.067 mg of coriander grass ethanol extract for the 0.067 group and a dose of 0.135 mg for the rat group 0.135. The results showed that there was an effect of increasing the performance of the rat uterus after administration of ethanol extract of coriander grass. It can be concluded that administration of the ethanol extract of the grass Biophytum petersianum Klotzsch kebar can increase uterine weight and uterine length of rats, with a good dose of 0.135 mg.